Things too huge to fix by saying sorry - Vaught, Susan, 1965- (Simon & Schuster Books for Young Readers, 2016)
"A family mystery leads Dani Beans to investigate the secrets of Ole Miss and the dark history of race relations in Oxford, Mississippi"--